Определение расчетного времени вынужденной эвакуации людей из зрительных залов зрелищных и культурно-просветительных учреждений с учетом индивидуальных особенностей эвакуируемых - Sobolevskiy С.; Dmitrichenko Александр; Poloz Денис (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
Article is devoted to definition of time of evacuation of people of premises with account heterogeneity of human stream. In base of offered approach concept of consideration of each person in human stream is placed how separate unit of account.